Collaborative State Apparatus Strategy in Countering Autonomous Drone Threats to the President and Vice President of the Republic of Indonesia - Pratama, Sigit Yudha (Security Intelligence Terrorism Journal (SITJ), 2025)
This research aims to develop a strategic collaboration model in addressing autonomous technology threats to high-ranking state officials, focusing on the integration of the roles of the Indonesian National Armed Forces (TNI), the Indonesian National Police (POLRI), and the State Intelligence Agency (BIN). Autonomous technology threats, particularly drones, are a primary concern in safeguarding the President and Vice President of the Republic of Indonesia. This study proposes the use of artificial intelligence (AI)-based technology to efficiently and swiftly detect and neutralize drone threats. Additionally, scenario-based simulations of modern threats are applied to enhance readiness and the effectiveness of security measures. The research employs a descriptive qualitative approach with a case study, involving primary data collection through in-depth interviews with relevant officials, as well as secondary data from literature studies and direct observations. The findings show that collaboration between TNI, Polri, and BIN, supported by AI technology and threat simulations, can strengthen the security system for high-ranking state officials in the digital era. This research contributes to the development of policies and strategies for more effective security measures in facing autonomous technology threats in Indonesia.